THE DIGITAL UNIVERSITY: CONCEPTUAL APPROACHES AND BIBLIOMETRIC ANALYSIS OF INTERNATIONAL AND KAZAKHSTANI RESEARCH - Tokhtar Bolatbek; Juzbayeva Zhansaya; Zakirova Dilnara (Theoretical Hypotheses and Empirical Results, 2026)
This article examines the conceptual foundations of the digital university and analyzes the dynamics of international and Kazakhstani scholarly discourse on this topic. Based on a bibliometric analysis of the Web of Science (WoS) database covering the period 1974-2026 (a sample of 1,170,245 documents), the study identifies key publication trends, including sustained long-term growth (CAGR 2000-2024: 8.37%), a pandemic-related acceleration in 2019-2022 (CAGR 17.76%), and subsequent stabilization of growth dynamics. The Kazakhstani sub-corpus (1,812 documents) demonstrates a pronounced pedagogical focus, with 32.29% of publications classified under Education & Educational Research, compared to 12.20% in the global corpus. The study systematizes the thematic contributions of Kazakhstani scholars and formulates theoretical and practical implications for the development of digital universities in the Central Asian context